Dampak Modifikasi Inlet Pipa terhadap Pengurangan Akumulasi Sludge dalam Oil Storage Tank - Kurniawan, Kurniawan; Kartawidjaja, Maria Angela; Sukwadi, Ronald; Cahyono, Budi (Universitas Batanghari Jambi, 2024)
PT. XYZ is a company that produces palm oil (CPO). In order to maintain the quality of sales, PT XYZ must be able to maintain the quality of what is stored in a storage tank called the Oil Storage Tank (OST). The aim of this research is to identify and analyze the factors that cause mutual problems in the quality of the bottom of the Oil Storage Tank (OST) and the most important thing is to reduce the pile of sludge that occurs due to the deposition process which cannot be recycled, thus causing a loss in the amount recorded in actually in the field when the Oil Storage Tank (OST) is washed. The more sludge deposits at the bottom of the tank, the higher the potential loss for the company. This research uses the PDCA (Plan, Do, Check, Action) method which based on the results of this research can reveal the impact of modifying the inlet pipe on the Oil Storage Tank (OST) on reducing the accumulation of sludge at the bottom of the Oil Storage Tank (OST) tank. The modification involves moving the pipe outlet to the middle of the bottom of the tank so that the sludge is distributed more evenly and makes it easier to suction when recycling it back to the processing process. As a result, the accumulation of sludge was reduced quite significantly from data from washing results in March 2023 of 23,430 kg and washing in January 2024 to 7,300 kg with a shelf life and total production of CPO (crude palm oil) stored in the Oil Storage Tank of around 20 thousand tons. over a period of 9 months.